2004
DOI: 10.1007/s10038-004-0166-z
|View full text |Cite
|
Sign up to set email alerts
|

A 1-Mb critical region in six patients with 9q34.3 terminal deletion syndrome

Abstract: Patients with 9q34.3 terminal deletion usually show a clinically recognizable phenotype characterized by specific facial features (microcephaly, flat face, arched eyebrows, hypertelorism, short nose, anteverted nostrils, carp mouth and protruding tongue) in combination with severe mental retardation, hypotonia, and other anomalies. We analyzed six unrelated patients with a various 9q34.3 terminal deletion. While having different-sized 9q34.3 deletions, all of these patients shared several distinctive anomalies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
1
19
0
2
Order By: Relevance
“…Deletion sizing in approximately 25 published patients has ranged from 380 kb (Patient 3, Kleefstra et al, 2006a) to greater than 3 Mb (Patient A, Harada et al, 2004) and has relied relatively low-resolution methods (e.g., FISH probes, low-density SNP, and microsatellite genotyping). There are no published accounts of precise (base pair resolution) breakpoint mapping of chromosome 9q microdeletions in the 9qSTDS.…”
Section: Unanswered Questions/future Directions Genotype/phenotype Comentioning
confidence: 99%
“…Deletion sizing in approximately 25 published patients has ranged from 380 kb (Patient 3, Kleefstra et al, 2006a) to greater than 3 Mb (Patient A, Harada et al, 2004) and has relied relatively low-resolution methods (e.g., FISH probes, low-density SNP, and microsatellite genotyping). There are no published accounts of precise (base pair resolution) breakpoint mapping of chromosome 9q microdeletions in the 9qSTDS.…”
Section: Unanswered Questions/future Directions Genotype/phenotype Comentioning
confidence: 99%
“…The syndrome is either caused by a submicroscopic deletion in the chromosomal region 9q34.3 or an intragenic mutation of the euchromatin histone methyltransferase 1 (EHMT1) gene causing haploinsufficiency of EHMT1 . So far, 85 patients, including 75 patients with a 9q34.3 deletion and 10 patients with an EHMT1 mutation, have been reported [Schimmenti et al, 1994;Ayyash et al, 1997;Dawson et al, 2002;Cormier-Daire et al, 2003;Font-Montgomery et al, 2004;Harada et al, 2004;Iwakoshi et al, 2004;Stewart et al, 2004;Neas et al, 2005;Yatsenko et al, 2005Yatsenko et al, , 2009Kleefstra et al, 2006aKleefstra et al, , b, 2009Stewart and Kleefstra, 2007;Verhoeven et al, 2010;Willemsen et al, 2011]. EHMT1 encodes a histone H3 Lys 9 methyltransferase and is thereby involved in chromatin remodeling [Ogawa et al, 2002].…”
mentioning
confidence: 99%
“…qter deletion or duplication without the involvement of another chromosome. Harada et al [1989] has described a case with similar de novo unbalanced translocation with comparable breakpoints, and recent molecular delineation of the breakpoint in the same patient by Harada et al [2004] showed that the deletion is larger than the shortest 1Mb deletion region overlap in other patients investigated in their recent studies. As seen from the CGH microarray studies, our patient also demonstrated a deletion exceeding this smallest deleted region (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Utilization of FISH techniques and CGH microarray technology in our family determined that the two subtelomeric probes were missing in the proband with retention of the ABL and ASS loci at 9q34.1. Additionally, based on the CGH microarray analysis, the deletion in our patient is larger than the smallest critical region of 1 Mb region determined by Harada et al [2004] as well as the 1.2Mb minimum commonly deleted region observed in the patients investigated by Stewart et al [2004].…”
Section: Discussionmentioning
confidence: 96%